Effect of fertilizer rates and soil series on root morphological traits and root: shoot ratio of immature natural rubber (Hevea brasiliensis) - Adekunle, Salisu Monsuru; Wan Daud, Wan Mohamed Noordin (IJSER Publications, 2016)
Report of this research emphasized the importance of roots morphological traits and root: shoot ratio (RSR) of selected clones of Hevea brasiliensis in nutrients utilization for the production of high vigor planting materials. Quantitative traits of root were examined with WinRHIZO image analysis; different from many previous similar studies on natural rubber. The study was conducted to determine the influence of fertilizer rates and soil series on three selected clones of natural rubber. It was observed that the fertilizer rates influenced root morphological traits such as root length, average diameter, surface area and root volume and root: shoot ratio (RSR). The root increases as fertilizer rates increase. Optimum level recommended for growth was 150% (234gm-2). The control had poor performance followed by 50% (78g m-2), and 100% (156g m-2). Holyrood (Ultisols) soil series promotes roots morphological traits when compared to Munchong (Oxisols) soil series. A high significant difference (p<0.5) was observed among the clones and RRIM 3001 had the best performance followed by RRIM 2001 while RRIM 2025 recorded least performance. Holyrood soil series (Ultisol) noticeably support root morphological traits of Hevea seedlings with fertilizer rate at 150%. Munchong (Oxisol) significayly support root: shoot ratio (RSR) at the same fertilizer rate. Both soils are suggested when considering the interaction between roots and shoot and the overral root morphology of the plant. The fertilizer rate is considered optimum for the rubber seedlings especially where RRIM 3001 is selected as planting material to be planted on any of the soils, Oxisols and Ultisols.